Prototype of Hand Dryer with Ultraviolet Light Using ATMega8 - Tatiya Padang Tunggal; Ahmad Wahyu Apriandi; Joessianto Eko Poetro; Elsayed T.Helmy; Farhad Waseel (Journal of Robotics and Control (JRC), 2020)
In everyday life, particularly in hospitals, people typically use cloth or tissue to dry our hands. It seems less practical, effective and hygienic. In addition, some restaurants still use cloth or tissue as well. To overcome this problem, several hospitals and restaurants have provided hand dryers. It can dry hands but cannot eliminate germs or bacteria. It is necessary to create a hand dryer equipped with a sterilizer. This work, therefore, created a hand dryer that can simultaneously dry and sterilize hands that worked automatically using the ATMega8 microcontroller. The tool was designed by using an infrared sensor to detect hands, and an ATMEGA8 microcontroller to read and process the sensors to activate UV and heating. The results found that the tool equipped with UV and heating can dry hands while eliminating bacteria and germs.